PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA GURU - Fourdiana, Rachmah; Hanafi, Ivan; Santosa, Heru (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to evaluate the impact of transformational leadership on teacher compensation and performance in Private Schools in Tambora District, West Jakarta. Compensation in this study includes financial rewards, such as salaries and benefits, as well as non-financial, such as work facilities, training, and appreciation. The correlational research method is used in a quantitative approach, with the location of the research in private schools in the sub-district. The results of the double correlation coefficient significance test showed significant differences in the regression model that explained the variability of teacher performance (F = 8.067, p = .001). In particular, Transformational Compensation and Leadership, as predictors, make a significant contribution in explaining variations in teacher performance. The Coefficients analysis highlights the positive and significant impact of Transformational Leadership (p = .008) and Compensation (p = .022) on teacher performance. These findings support the hypothesis that improved Transformational Leadership and Compensation can improve teacher performance. The implications of this study show the importance of implementing transformational leadership and an adequate compensation system in improving the quality of education in private schools in Tambora District, West Jakarta. Transformational leadership can drive teacher and staff motivation, innovation, and performance, while a decent compensation system can increase job motivation and retain qualified educators. Keywords: Transformational Leadership; Compensation; Teacher Performance